A Novel Therapeutic Approach for Colorectal Cancer Stem Cells: Blocking the PI3K/Akt Signaling Axis With Caffeic Acid - Park, Se-Ra; Kim, Soo-Rim; Hong, In-Sun; Lee, Hwa-Yong (Frontiers in Cell and Developmental Biology, 2020)
Colorectal cancer stem cells (CSCs) are resistant to conventional chemotherapeutic drugs and radiation, which may destroy tumor masses but not all colorectal CSCs, contributing to tumor metastasis and relapse. However, it is very difficult to selectively target and eliminate CSCs because they share many common pathologies and features of normal stem cells. Therefore, finding novel compounds and therapeutic strategies that selectively target colorectal CSCs will help eradicate malignancies. In the present study, we showed that caffeic acid effectively suppresses clonogenic potential, the proportion of CD44+CD133+ cells, stem-like properties, and migratory capacity of colorectal CSCs in vitro and in vivo. Notably, our clinical data analysis also revealed that PI3K/Akt signaling may be linked to multiple colorectal CSC-associated characteristics, such as radio-resistance, stem-like property, and tumorigenic potential. To the best of our knowledge, this is the first study demonstrating that caffeic acid effectively targets colorectal CSC populations by inhibiting the growth and/or self-renewal capacity of colorectal CSCs through PI3K/Akt signaling in vitro and in vivo.